Generations, Inc. : from boomers to linksters--managing the friction between generations at work - Johnson, Meagan, 1970-; Johnson, Larry, 1947- (AMACOM, 2010)
When Woodstock meets Facebook at the watercooler.
Keywords: Diversity in the workplace -- Management.; Intergenerational relations.; Intergenerational communication.; Conflict of generations.; Personnel management.; elektronické knihy; electronic books